Optimalisasi Pengawasan Oleh DPRD Dalam Pelaksanaan Pembangunan Di Kabupaten Pangandaran - Solihudin Solihudin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to obtain an answer in research on Optimization of Oversight by the DPRD in the Implementation of Development in Pangandaran Regency. This study uses a qualitative method with a case study approach intended to get phenomena in the field so as to produce descriptive data in the form of written words. Techniques in collecting data in this study is to use technical observation, interviews and documentation. The results of this study indicate that the optimization of oversight by the DPRD in implementing development in Pangandaran Regency has not been effective in its implementation. This is based on the measurement theory put forward by Paulus Effendie Lotulung in (Fachrudin, 2004:93) types of supervision in terms of execution time are divided into two types: 1) a-priori control and 2) a-posteriori control. the solution to the problem that occurs is to continue to pay attention and follow up on work in supervising development in Pangandaran Regency so that the development is effective and goes according to the agreement made in the district Musrenbang and this becomes the main basis for implementing development in Pangandaran Regency.